1998
DOI: 10.1038/sj.bjp.0701643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trimetazidine and verapamil on the cardiomyopathic hamster myosin phenotype

Abstract: 1 In this study we investigated whether long-term trimetazidine (anti-ischaemic drug) therapy alters the ventricular myosin heavy chain (MHC) isoform composition in a model of cardiomyopathy. 2 MHC isoforms were analysed in the native state by electrophoresis in a pyrophosphate buer. Myosin isoform patterns were studied in cardiac muscle from cardiomyopathic hamsters (CMH) of the BIO 14 : 6 strain during the time course of the disease and compared with those of healthy golden hamsters (F1B). The correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Long‐term oral treatment with TMZ efficiently decreased Ca 2+ overload and hypertrophy in cardiomyopathic Syrian hamster (CMH) of the strain BIO 14:6, which is a model for both cardiac and skeletal muscle abnormalities, to the levels of normal Syrian hamsters (F1B) (D'hahan et al 1997). The same authors later attempted to prevent the redistribution of myosin phenotype from V1 to V3 with TMZ and a Ca 2+ channel blocker, verapamil, but failed to show an association between the effects of the drugs on hypertrophy and on myosin isoforms (D'hahan et al 1998). The authors concluded that the positive effects with long‐term TMZ therapy might be related to the maintenance of V3 isoform that has a lower ATPase activity and thus utilizes less energy through an unknown mechanism (D'hahan et al 1998).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term oral treatment with TMZ efficiently decreased Ca 2+ overload and hypertrophy in cardiomyopathic Syrian hamster (CMH) of the strain BIO 14:6, which is a model for both cardiac and skeletal muscle abnormalities, to the levels of normal Syrian hamsters (F1B) (D'hahan et al 1997). The same authors later attempted to prevent the redistribution of myosin phenotype from V1 to V3 with TMZ and a Ca 2+ channel blocker, verapamil, but failed to show an association between the effects of the drugs on hypertrophy and on myosin isoforms (D'hahan et al 1998). The authors concluded that the positive effects with long‐term TMZ therapy might be related to the maintenance of V3 isoform that has a lower ATPase activity and thus utilizes less energy through an unknown mechanism (D'hahan et al 1998).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…The same authors later attempted to prevent the redistribution of myosin phenotype from V1 to V3 with TMZ and a Ca 2+ channel blocker, verapamil, but failed to show an association between the effects of the drugs on hypertrophy and on myosin isoforms (D'hahan et al 1998). The authors concluded that the positive effects with long‐term TMZ therapy might be related to the maintenance of V3 isoform that has a lower ATPase activity and thus utilizes less energy through an unknown mechanism (D'hahan et al 1998).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…The cardiomyopathy is apparent at Ϸ10 weeks of age and becomes clinically apparent at 17 weeks of age. [13][14][15][16][17][18][19][20] Therefore, BIO 53.58 hamsters provide a good model of dilated cardiomyopathy. We used 4-week-old BIO 53.58 hamster cardiomyocytes as transplant donors.…”
Section: Discussionmentioning
confidence: 99%
“…Trimetazidine exerts its protective effects by preventing ATP levels from decreasing and limiting free radical, proton, sodium and calcium ion accumulation in cardiomyocytes (20)(21)(22). The efficacy of trimetazidine administered to young animals has been previously reported in CMH (9,(23)(24); however, it is not known whether trimetazidine can also preserve cardiac NKA activity and isoform expression in the CMH model and in long-term follow-up. Using the experimental design of a trimetazidine treatment with a long-term follow-up, the present study aimed to i) characterize NKA activity in relation to the expression of its α and β subunits in the CMH model, ii) determine whether long-term trimetazidine treatment could prevent NKA alterations and iii) define the relationship between membrane NKA changes and cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%